Pendampingan Dan Bantuan Hukum Terhadap Anak Di Bawah Umur Yang Menikah Di Bawah Tangan Di Desa Munggu - Handayani, Holinda; Anggelina, Devina; Anugrah , Muhammad (Universitas Pahlawan Tuanku Tambusai, 2024)
Underage marriage is still a problem in Indonesia even though it has been regulated in Law Number 16 of 2019 concerning marriage which stipulates the minimum age of marriage is 19 years old. In Munggu Village, informal or underhand early marriage is still frequent, mainly influenced by social, cultural, and economic norms. This practice of marriage without official registration results in a lack of legal protection for the children involved, as well as the loss of their access to civil rights such as inheritance rights and other legal guarantees. In addition, early marriage has the potential to pose physical and mental health risks, especially for girls who are not yet biologically ready. This project aims to break the cycle of early marriage in Munggu Village through socialization, education, as well as mentoring and legal assistance for the community. The implementation of the activity was carried out for four months with a series of activities such as field surveys, socialization related to the negative impact of early marriage, as well as legal assistance to legitimize the marital status of the couples involved. The results of this project show an increase in public awareness regarding the impact of child marriage and successfully help couples who marry underage obtain legality through KUA. The community's participation in this activity is very good, and this project is expected to provide sustainable legal protection and increase legal awareness in the future. This project contributes to educating the public about the importance of preventing early marriage and providing legal support for those involved in child marriage, as well as encouraging the formation of a more law-aware society.